Potensi Spiritual Manusia: Upgrading Transformasi Rohani Sebagai Rekontruksi Pemahaman Mendalam Berdasarkan Ajaran Islam - Mukhlis Mukhlis (STIT Syekh Muhammad Nafis Tabalong, 2024)
This research aims to explore the process of upgrading spiritual transformation as a reconstruction of a deep understanding of human spiritual potential. Human spiritual potential is a complex and profound dimension of human existence. This concept encompasses inner experiences, relational existence with the universe, and the search for meaning in life. Efforts to understand human spiritual potential require recognition of the changes and transformations that occur in the spiritual dimension. The methods used include literature review from various disciplines, including psychology, spirituality, and philosophy. The research findings indicate that efforts to enhance human spiritual potential require awareness of the ongoing transformation process. In this context, a deep reconstruction of understanding human spiritual potential necessitates a holistic and integrated approach. This involves combining traditional spiritual practices with contemporary understandings of psychology and neuroscience. Additionally, it is important to consider the social and cultural aspects in the development of individual and collective spirituality. This study emphasizes the importance of understanding human spiritual potential as a dynamic process involving the upgrading of spiritual transformation. A deep reconstruction of understanding the dimensions of human spirituality can provide a foundation for a more holistic and sustainable self-development in the context of this complex modern life.